1996
DOI: 10.1007/bf00170829
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterisation of P2 purinoceptors in PC12 cells by measurement of radiolabelled calcium influx

Abstract: The aim of this study was to determine whether 45Ca2+ influx could be used as a quantitative measure of channel activation for functional characterisation of P2X purinoceptors in cell lines. In undifferentiated PC12 cells, grown in suspension, ATP (EC50 = 45 microM), ATP gamma S (EC50 = 50 microM) and 2-meSATP (EC50 = 81 microM) but not alpha beta meATP (1 mM) stimulated 45Ca2+ influx 2-5 fold. This effect did not appear to be due to activation of P2U or P2Y purinoceptors since 1 mM UTP, ADP or ADP beta S did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 39 publications
5
43
0
1
Order By: Relevance
“…A nervous system-specific P2X receptor subtype, P2X2, was initially cloned from PC12 cells and exhibits a distinctive pharmacological profile (10) and has been implicated in mediating many of the biological actions of ATP. Michel et al (11) have recently demonstrated that the P2X2 receptor appears to be principally responsible for the ATPstimulated calcium influx in PC12 cells, extending and confirming a number of earlier reports of the involvement of the P2X subclass in mediating the action of ATP.…”
supporting
confidence: 66%
See 3 more Smart Citations
“…A nervous system-specific P2X receptor subtype, P2X2, was initially cloned from PC12 cells and exhibits a distinctive pharmacological profile (10) and has been implicated in mediating many of the biological actions of ATP. Michel et al (11) have recently demonstrated that the P2X2 receptor appears to be principally responsible for the ATPstimulated calcium influx in PC12 cells, extending and confirming a number of earlier reports of the involvement of the P2X subclass in mediating the action of ATP.…”
supporting
confidence: 66%
“…The ATP-stimulated calcium influx (11) and MAP kinase activation in PC12 cells is a consequence of the activa- ). B, the two PC12 cell lines, the line used in this study (left panels), and the line obtained from Dr. S. Soltoff (right panels) were deprived of serum for 16 h and then treated with 100 mM ATP, UTP for 2 min or 50 ng/ml NGF for 5 min.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that RB-2 inhibits ectonucleotidase activity in X. laevis oocytes and ATP-induced inflammation of the mouse hind paw . The inhibitory effects of RB-2 were also observed in currents and calcium measurements in single PC12 cells (Nakazawa et al, 1991;Michel et al, 1996) as well as in experiments with cells expressing recombinant rP2X1R and P2X2R (Surprenant, 1996). For a more detailed description of the antagonistic actions of RB-2, see Ralevic and Burnstock (1998).…”
Section: A P2x Receptor Agonism and Antagonismmentioning
confidence: 86%